1999
DOI: 10.1177/004728759903700311
|View full text |Cite
|
Sign up to set email alerts
|

Profiling People Searching for and Purchasing Travel Products on the World Wide Web

Abstract: This study provides a profile of people who use the Internet to gather travel information or to purchase travel arrangements. Compared to other World Wide Web users, those who search for or purchase travel on-line are more likely to be 26 to 55 years of age; to have higher incomes; to be employed in management, professional, or computer-related occupations; and to have more years of experience on-line. Concerns about credit card security, evaluation of product quality, and privacy issues are problems that on-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
126
3
7

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(155 citation statements)
references
References 10 publications
19
126
3
7
Order By: Relevance
“…However, individuals between the ages of 25 to 55, possessing higher levels of education and income, were more likely to purchase travel online. Effectively, the majority of the succeeding studies also found that travelers with higher education levels were more likely to purchase travel online (Heung, 2003;Kamarulzaman, 2007Kamarulzaman, , 2010Kim & Kim, 2004;Law, Leung, & Wong, 2004;Lee, Qu, & Kim, 2007;Li & Buhalis, 2006;Morrison, Jing, O'Leary, & Cai, 2001;Wolfe, Hsu, & Kang, 2004), but not without some contradictory evidence (e.g., Weber & Roehl, 1999). In fact, in Morrison et al's model (2001), education was found to be the only sociodemographic variable that affected the likelihood of using the Internet to purchase travel.…”
Section: Demographic Variablesmentioning
confidence: 97%
See 1 more Smart Citation
“…However, individuals between the ages of 25 to 55, possessing higher levels of education and income, were more likely to purchase travel online. Effectively, the majority of the succeeding studies also found that travelers with higher education levels were more likely to purchase travel online (Heung, 2003;Kamarulzaman, 2007Kamarulzaman, , 2010Kim & Kim, 2004;Law, Leung, & Wong, 2004;Lee, Qu, & Kim, 2007;Li & Buhalis, 2006;Morrison, Jing, O'Leary, & Cai, 2001;Wolfe, Hsu, & Kang, 2004), but not without some contradictory evidence (e.g., Weber & Roehl, 1999). In fact, in Morrison et al's model (2001), education was found to be the only sociodemographic variable that affected the likelihood of using the Internet to purchase travel.…”
Section: Demographic Variablesmentioning
confidence: 97%
“…In their seminal study, Weber and Roehl (1999) found that there were no differences between online purchasers and nonpurchasers regarding gender and race. However, individuals between the ages of 25 to 55, possessing higher levels of education and income, were more likely to purchase travel online.…”
Section: Demographic Variablesmentioning
confidence: 99%
“…Em u ma análise dos diversos tipos de riscos percebidos encontrados na literatura supõe-se que as compras pela Internet podem desencadear alguns novos tipos de risco, como por exe mplo, o risco da privacidade e segurança das informações transmitidas (MIYAZAKI e FERNANDEZ, 2000;WEBER e ROEHL, 1999;GONÇALVES et al, 1998;LASCH, 1998;ROHM e MILNE, 1998).…”
Section: Risco Percebido Nas Compras Pela Internetunclassified
“…Além da privacidade e segurança, outros tipos de riscos percebidos foram encontrados na literatura para as compras realizadas pela Internet, como: o risco social, de performance, satisfação e tempo (WEBER e ROEHL, 1999;HOFFMAN, 1996).…”
Section: Risco Percebido Nas Compras Pela Internetunclassified
“…For instance, Au and Hobson (1997) report that millions of consumers are accessing the Internet to seek out travel-related products and services. Given the product-to-consumer nature of the hospitality and tourism industry it is not surprising to find that the Internet has inspired research in areas such as consumer product trial, loyalty development, market penetration, lead generation, and the determination of consumer usage patterns (Weber & Roehl, 1999;Bonn, Furr, & Susskind, 1999). Furthermore, this heightened level of matching the consumer-to-product cycle is best captured by publications devoted to Internet marketing (Kent & Calishain, 1999;Silverstein, 1999) and works devoted to e-commerce (Camp & Sirbu, 1997;Peterson, Balasubramanian, & Bronnenberg, 1997).…”
Section: Introductionmentioning
confidence: 99%